Kendali dan Monitoring Ruang Server dengan Sensor Suhu DHT-11, Gas MQ-2 serta Notifikasi SMS - Firdiansyah Firdiansyah; Siswanto Siswanto; Muhammad Anif; Basuki Hari Prasetyo (Prosiding SISFOTEK, 2019)
If the server room temperature is too hot it will cause damage to the existing hardware in the server room, whereas if the gas threshold is too high it will be able to indicate that a fire has occurred in the server room. One way to maintain the temperature level of 20-21ºC / (68-71ºF) and 350 ppm - 1000 ppm gas levels in the server room is to periodically monitor the temperature and gas content whether it is within the threshold that we specify ... So that if one day there is a deviation temperatures outside the tolerance range can be immediately taken responsive measures. Currently the server administrator must continue to monitor changes in temperature in the server room in stable condition and still manually. Temperature and gas monitoring systems and web-based control using DHT11 sensors and MQ-2 sensors can be one solution to monitor the temperature of the server room so that it is always in a conducive state, so as to minimize the occurrence of excess heat in devices in the server room . If there is a situation where changes in temperature and gas in the server room are detected, the system will send a notification to the user via SMS and automation of the additional air conditioning so that it can stabilize the room temperature again. Thus the temperature and gas of the server room will continue to be maintained and stable in full control by the server administrator without having to continue to be in the server room. The programming language used to create this system is the Arduino programming language whose syntax resembles the C language and for its visual appearance using the PHP programming language and MySQL database. From the observation of 23 days the application trial was able to run and give notification as much as 98% and system failure as much as 2%.